2021
DOI: 10.1111/jce.15070
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh density atrio‐ventricular dual‐chamber mapping as a next generation tool for ablation of accessory pathways

Abstract: Introduction Detailed three‐dimensional (3D) mapping has been useful for effective radiofrequency catheter ablation. The Rhythmia system can create atrio‐ventricular dual‐chamber mapping, which reveals the atrial and ventricular potentials all at once in the same map. The aim of this study was to investigate the utility of mapping the atrium and ventricle simultaneously with a high‐density 3D mapping system for the ablation of accessory pathways (AP). Methods From July 2015 to August 2020, 111 patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Three-dimensional electroanatomical mapping offers a highdensity map for the visualization of pathway conduction. 4,5 To date, the efficacy of OWM with the EEML algorithm has only been described in a case report. 6 In this two-center study, we showed that high-density OWM with automatic annotation of local electrograms and using the EEML algorithm not only achieved a high AP elimination rate by the first RF application but also revealed broad APs requiring multiple ablation lesion sets for AP elimination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three-dimensional electroanatomical mapping offers a highdensity map for the visualization of pathway conduction. 4,5 To date, the efficacy of OWM with the EEML algorithm has only been described in a case report. 6 In this two-center study, we showed that high-density OWM with automatic annotation of local electrograms and using the EEML algorithm not only achieved a high AP elimination rate by the first RF application but also revealed broad APs requiring multiple ablation lesion sets for AP elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the conventional point‐by‐point mapping may result in an incorrect annotation of the correct chamber, which may cause difficulty in eliminating the APs. Three‐dimensional electroanatomical mapping offers a high‐density map for the visualization of pathway conduction 4,5 . To date, the efficacy of OWM with the EEML algorithm has only been described in a case report 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mori et al reported the use of the Rhythmia mapping system in identifying APs in 128 patients creating high-density atrioventricular dual chamber maps with subsequent ablations at the earliest activation site on the atrioventricular annulus. [ 23 ] Similarly, the OWM technique can also be used with the Rhythmia mapping system. The novel LUMIPOINT software module (Boston Scientific) may also assist in identifying the AP locations.…”
Section: Specific Mapping System Considerationsmentioning
confidence: 99%